Perlindungan Hukum Terhadap Perempuan Korban Kekerasan Dalam Rumah Tangga di Kota Tangerang Selatan - Sylvia Amanda; Dian Puji Simatupang (STAATSRECHT: Indonesian Constitutional Law Journal, 2019)
AbstractViolence against women is an act that is contrary to human rights. That is why the act of violence against women is one of the acts that violates human rights, so we need a national legal instrument regarding the elimination of violence against women in Indonesia. The purpose of this research is to find out what are the factors of women becoming victims of domestic violence, and to find out legal protection efforts for women victims of domestic violence. The analysis used in this research is descriptive which uses qualitative research types with the aim of revealing facts, circumstances, phenomena and circumstances when researching. The results of this study indicate factors that cause women to become victims of domestic violence, such as individual factors, partner factors, socio-cultural factors, and economic factors, and efforts to protect the law of women victims of domestic violence are regulated in the Criminal Code, Law Number 23 of 2004 concerning Elimination of Domestic Violence. Forms of legal protection directly through institutions such as Integrated Service Centers and Legal Aid Institutions.Keywords: Violence, Household, Legal Protection